การจัดการการสื่อสารเพื่อพัฒนาความผูกพันศิษย์เก่าของมหาวิทยาลัยรัฐในประเทศไทย - มีเคลือบ อนวัช; ชาญวิชัย กิตติมา; วีรังกร จิรวัฒน์ (Journal of Business, Innovation and Sustainability (JBIS), 2017)
งานวิจัยนี้ มีวัตถุประสงค์เพื่อศึกษาการจัดการการสื่อสารที่ใช้ในการพัฒนาความผูกพันศิษย์เก่าของมหาวิทยาลัยรัฐในประเทศไทย เป็นการวิจัยเชิงคุณภาพใช้การสัมภาษณ์เชิงลึก (In - depth Interviews) และการสนทนากลุ่ม (Focus Group Discussion) จากผู้ให้ข้อมูลที่เป็นผู้บริหารมหาวิทยาลัย บุคลากรงานศิษย์เก่าสัมพันธ์และศิษย์เก่า ผลการวิจัยพบว่า การจัดการการสื่อสารทั้ง 3 ด้าน มีรายละเอียดดังนี้ 1) ด้านองค์ประกอบการสื่อสาร มหาวิทยาลัยควรมีการกำหนดค่านิยมร่วม วัฒนธรรม ประเพณีของสถาบัน ใช้การสื่อสารกลุ่มย่อยระดับเครือข่าย กลุ่มใหญ่ระดับสถาบันใช้สื่อใหม่ สื่อมัลติมีเดีย ในการเผยแพร่ข้อมูลข่าวสาร ให้ความสำคัญกับการเชิญศิษย์เก่าเข้าร่วมกิจกรรม มีการสื่อสารแบบเป็นทางการกับศิษย์เก่าอาวุโส 2) ด้านนโยบายและระบบสื่อสาร มหาวิทยาลัยควรกำหนดโครงสร้างหน่วยงานดูแลชัดเจน มีสมาคม ชมรม มีฐานข้อมูลศิษย์เก่าเพื่อสร้างความสัมพันธ์ จัดกิจกรรมประเพณี กำหนดยุทธศาสตร์ แผนพัฒนานักศึกษาเน้นศิษย์เก่าเข้ามามีส่วนร่วม ให้ความสำคัญกับศิษย์เก่าต่างชาติ (ประเทศเพื่อนบ้าน) ยกย่องเชิดชูศิษย์เก่าด้วยรางวัลที่หลากหลาย กิจกรรมต้องเกิดจากความต้องการของศิษย์เก่า พัฒนาความสัมพันธ์ไปยังผู้มีส่วนเกี่ยวข้อง และ 3) ด้านการประเมินการจัดการ มหาวิทยาลัยควรสร้างรูปแบบการใช้ชีวิตในมหาวิทยาลัย (University life) ให้สมบูรณ์ เช่น หอพัก กิจกรรมรับน้อง การเรียน กีฬา ชมรม มีการกำหนดแผนการจัดประชุมใหญ่ รวมทุกสมาคม ชมรม ประจำปี เพื่อวางแนวทางการจัดกิจกรรม บูรณาการกิจกรรมพัฒนานักศึกษากับศิษย์เก่าสัมพันธ์ ไม่ควรมุ่งเน้นการระดมทุนจากศิษย์เก่า The State-of-the-Art Communication Management for Developing Alumni’s Engagement in Public Universities of Thailand This research aims to study the Communication Management for Developing Alumni’s Engagement in Public Universities of Thailand. It is the Qualitative Research using in - depth Interviews and Focus Group Discussion from the samples who are universities’ administrators, officer of alumni relations and alumni. The details of the research are in 3 parts which are 1) Communication elements: The universities should have the shared values, culture and tradition for the institutes to communicate with minor group network. Major universities group should use new media and multimedia to publicize and invite alumni to join their activities. There should also be a formal communication with senior alumni; 2) Policy and Communication System: The universities should define an organization structure which specifically serve Alumni Relations. There should be an association, club, alumni data-base to make relations, create traditional activities, set strategic plan/development plan for students, persuade alumni to participate in activities, contact foreign alumni (Thailand’s neighboring countries), praise alumni by giving varieties of awards. All activities must be created based on the needs of Alumni, and develop relations with other related people; and 3) management evaluation: The universities should make the “University life” to be comprehensive such as dormitories, new student welcoming activities, study, sports, clubs. There should be annual meetings which include all associations and clubs to create activities and integrate activities to develop students and alumni without money donating. DOI: http://dx.doi.org/10.14456/becj.2017.13